In Vitro Activities of SCH27899 Alone and in Combination with 17 Other Antimicrobial Agents - Fuchs, Peter C. (American Society for Microbiology, 1999)
SCH27899, an everninomicin antibiotic, was tested for its in vitro activity against 718 bacterial isolates representing 27 species. The Enterobacteriaceae and nonenteric gram-negative bacilli were resistant to ≥8.0 μg/ml, but all others were inhibited by ≤1.0 μg/ml. When tested in combination with 17 other antimicrobial agents against 110 strains, SCH27899 demonstrated no significant antagonism or synergy. Consequently, combination therapy is not contraindicated.